The Correlation Between Metacognitive Reading Strategies, Vocabulary Mastery and Reading Comprehension of The Ninth-Grade Students In SMP Negeri Hindu 2 Payangan - Ni Putu Pebriyanti; Ni Made Ratminingsih; Made Hery Santosa (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Reading is a process of getting information and understanding the message of printed material. The research objective was to know 1) How much do metacognitive reading strategies contribute to students’ reading comprehension of ninth- grade students. 2)How much does vocabulary mastery contribute to students’ reading comprehension in the ninth-grade students in SMPN 2 Payangan. 3) How much do metacognitive reading strategies and vocabulary mastery simultaneously contribute to students’ reading comprehension of the ninth-grade students. The research instruments, tests and questionnaire, were administered to collect the required data. The samples of this study were 164 students. They were selected through total sampling technique. Linear regression and multiple regression were carried out to analysis the data that assisted by SPSS 26.0 version. Based on the results of the research instruments, it could be concluded. The contribution of students’ metacognitive contribute of 33,3% towards reading comprehension and there is a significant contribution of metacognitive reading strategies to students’ reading comprehension of the ninth-grade students in SMPN 2 Payangan in the academic year 2023/2024. Moreover, students’ vocabulary mastery contributes 50,8% towards reading comprehension and there is a significant contribution of metacognitive reading strategies to students’ reading comprehension of the ninth-grade students in SMPN 2 Payangan, and the contribution of metacognitive reading strategies and vocabulary mastery to students’ reading comprehension was 35.1%. There is a significant contribution of metacognitive reading strategies to students’ reading comprehension of the ninth-grade students in SMPN 2 Payangan.